PENINGKATAN KUALITAS PEMBELAJARAN MATA KULIAH BERMAIN DAN PERMAINAN MELALUI KEGIATAN LESSON STUDY - Mutiara Magta (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
The implementation of lesson study activity intended to enhance the learning quality within the university. The lesson study conducted in four cycles on Play and Learning module at Department of Early Childhood and Teacher Education (PG-PAUD), Faculty of Education, Ganesha Educational University. The findings in term of the lesson study activity showed: (1) the increasing professionalism of the lecturers’ performance in the field of teaching where they become more aware in arranging the lesson plan, more prepared in mastering the learning process, more alert into the evaluation, and increase the collaboration among lectures; (2) the increasing of meaningful learning quality; and (3) developing students’ character.